Implementation of Integrated Marketing Communication in Image of Private Higher Education - Dikdik Harjadi; Dewi Fatmasari (Faculty of Economics and Business, University of Pasundan, 2017)
This study aimed to examine the implementation of integrated marketing communication conducted by private universities in Kuningan Regency and analyze the influence of integrated marketing communication performance which includes advertising, sales promotion, personal selling, public relation, and direct marketing on private university image. The method used was descriptive and verificative method conducted by collecting primary data in the field from private university students in Kuningan Regency. Based on the results of data processing and hypothesis testing, it was known that integrated marketing communication consisting of advertising, personal selling, sales promotion, public relation, and direct marketing simultaneously and partially had a positive and significant impact on private university image. The simultaneous influence is 38.7%, which meant there was still much influence outside the implementation of integrated marketing communication that affected private university image. The biggest influence was sales promotion.